(untitled) (Journal of actual problems of jurisprudence, 2018)
The urgency of the article is determined by the following factors: the acceleration of digital modernization in Kazakhstan under the application of global informatization leads to the transition to electronic document circulation; Increasing the efficiency of the Kazakh government through the introduction of information technology; the task is to accelerate the economic and political modernization of Kazakhstan’s society through the extensive use of information technologies, as well as theoretical and practical interest in studying the potential benefits of e-government and electronic document management. Key words: electronic government, electronic digital signature, electronic document management, state services, digitalization, legal regulation.